Digital Media and Storytelling in Higher Education - Anita Lanszki (L'Harmattan Open Access, 2022)
Anita Lanszki's book is about storytelling in the digital media environment. The enterprise is both classical in that it explores the nature of storytelling, which is found in all historical periods and human communities, and modern in that it undertakes a broad overview of contemporary digital culture from the perspective of storytelling. The book is also a methodological guide, illustrated with numerous examples, which has emerged organically from the author's many years of teaching experience. Although the title reflects a focus on the use of digital storytelling in various fields of higher education and research, this excellent work can also be used by professionals working in other spheres of education. Whatever our views on the digital space and age may be, we can probably all agree that we are witnessing a democratization of storytelling in our time. The insights in this book are therefore extremely useful for anyone who is interested in how the timeless practice of storytelling is adapting to the new media environment.